Investigative study of stress effect on control of blood glucose level hyperglycemia - Azmi, Nurliyana Izyani (2019)
Stress hormones such as cortisol, glucagon, epinephrine and epinephrine play an important role in affecting the blood glucose level in human body. Based on previous studies, increased stress hormones have caused the blood glucose level to elevate. A sudden increase of blood glucose level in patients body may lead to the occurrence of hyperglycemia when the blood glucose level is above the normal baseline. Thus, the objectives of this study are to determine the effect of stress on the control of blood glucose level by simulating an algorithm to control the blood glucose level by using a Rudimentary model. The simulation study was carried out by using MATLAB on virtual patient through the application of in-silico method. However, in this paper attention was focused solely on cortisol only and other stress hormones were neglected due to limited data. In conclusion, blood glucose level can be controlled through the simulation.